Interdisciplinary three-step strategy to treat aortic stenosis and coronary artery disease in a patient with end-stage chronic obstructive pulmonary disease - Schmitz C; Beiras-Fernandez A; Sodian R; Wolf M; Kaczmarek I; Bigdeli AK; Michel S (Dove Medical Press, 2012)
Sebastian Michel1, Amir K Bigdeli1, Andres Beiras-Fernandez2, Christoph Schmitz1, Manuel Wolf1, Ralf Sodian1, Ingo Kaczmarek11Department of Cardiac Surgery, Ludwig Maximilians University of Munich, Munich, Germany; 2Department of Thoracic and Cardiovascular Surgery, Goethe University Frankfurt, Frankfurt am Main, GermanyBackground: Valvular aortic stenosis is a common disease in the elderly, often in multimorbid patients. It is often associated with coronary artery disease and peripheral artery disease. In this situation, the risk of conventional open-heart surgery is too high, and other treatment strategies have to be evaluated.Case report: A 79-year-old female patient with severe aortic stenosis, coronary artery disease and end-stage chronic obstructive pulmonary disease suffering from dyspnea at rest and permanently dependent on oxygen was treated in three steps. Firstly, her pulmonary infection was treated with antibiotics for 7 days. Then, the left anterior descending artery was stented (bare-metal stent). In the same session, valvuloplasty of the aortic valve was performed. She was sent to rehabilitation to improve her pulmonary condition and took clopidogrel for 4 weeks. Finally, she underwent transapical aortic valve replacement. She was released to rehabilitation on postoperative day 12.Conclusion: A combination of modern interventional and minimally invasive surgical techniques to treat aortic stenosis and coronary heart disease can be a viable option for multimorbid patients with extremely high risk in conventional open-heart surgery.Keywords: aortic stenosis, transapical aortic valve replacement, minimally invasive cardiac surgery